A comparative analysis of scores and chronological age of participants in the 2017-2020 Olympic cycle individual Rhythmic Gymnastics Continental Championships - Sterkowicz-Przybycien, K. (Journal of Physical Education and Sport, 2022)
Comparing the scores of performances and chronological age in participants of Rhythmic Gymnastics Continental Championships in one Olympic cycle (2017-2020) has the potential to indicate the global differences in the development of this sport. The aim of the study was to, 1) identify the events characterized by the highest/lowest gymnasts` achievements based on judges scores, and determine the differences in total scores, difficulty and execution of all-around, hoop, ball, clubs and ribbon in qualification competition, and finals, across Continental Championships (CC), and 2) compare the chronological age of CC participants. The material was obtained from the official RG Results Books and official documents of five Continental Championships. The total sample included individual rhythmic gymnasts (n=116) that participated in all-around and finals of: 15th African Championships (ACh), Sharm El Sheikh, EGY, (n=15); Oceania RG CC (OCh), Carrara, QLD, AUS, (n=17); 12th Senior Rhythmic Gymnastics Asian Championships (AsCh), Tashkent, UZB, (n=11); 37th European Championships in Rhythmic Gymnastics (ECh), Varna, BUL, (n=52); Rhythmic Gymnastics Senior Pan American Championships (PACh), Rio de Janeiro, BRA, (n=21). For each final (hoop, ball, clubs, ribbon), the eight qualified gymnasts` scores were compared except for OCh where only six gymnasts for each apparatus qualified. The gymnasts` chronological age was also calculated. The Kruskal-Wallis test and a post-hoc Bonferroni test at the 95% confidence level were used. The comparative analysis determined the events that were characterized by the highest or lowest judges` scores and showed significant differences in total, difficulty, and execution scores for hoop, ball, clubs, and ribbon between all-around qualification competitors (p<0.001), and between apparatuses finalists (p<0.001) across CC participants. The chronological age significantly differentiated participants in all-around competition (H=12.6, p<0.01, n^2=0.078) showing gradation from the youngest to the oldest: ACh<OCh<ECh<AsCh<PACh. Moreover, the ball and ribbon ECh finalists were significantly older from those of OCh and ACh finalists (p<0.001). The results of the present study may be used in future analysis of scores and chronological age of rhythmic gymnasts representing particular CC to monitor the trend between front rank events` competitors and those with lower achievements. This can be informative for gymnastics federations and state institutions that are able to organizationally and systemically support the sport development.